Retrospective analysis of effectiveness of fingolimod in real life setting in Turkey (REFINE) - Tuncer, Asli; Kurtuncu, Murat; Terzi, Murat; Uygunoglu, Ugur; Goncuoglu, Cansu; Yuceyar, Ayse Nur; Eraksoy, Mefkure (Tubitak Scientific & Technological Research Council Turkey, 2023)
Background/aim: During multiple sclerosis (MS) treatment different modes of action such as lateral (interferon beta to glatiramer acetate or glatiramer acetate to interferon beta) or vertical (interferon beta/glatiramer acetate to fingolimod) drug switch can be performed. This study aims to investigate the clinical effectiveness of switching from the first-line injectable disease modifying treatments (iDMTs) to fingolimod (FNG) compared to switching between first-line iDMTs.Materials and methods: This is a multicenter, observational and retrospective study of patients with relapsing-remitting MS who had lateral and vertical switch. The observation period included three key assessment time points (before the switch, at switch, and alter the switch). Data were collected from the MS patients' database by neurologists between January 2018 and June 2019. The longest follow-up period of the patients was determined as 24 months after the switch.Results: In 462 MS patients that were included in the study, both treatments significantly decreased the number of relapses during the postswitch 12 months versus preswitch one year while patients in the FNG group experienced significantly fewer relapses compared to iDMT cohort in the postswitch 12 months period. FNG cohort experienced fewer relapses than in the iDMT cohort within the postswitch 2 year. The mean time to first relapse after the switch was significantly longer in the FNG group.Conclusion: The present study revealed superior effectiveness of vertical switch over lateral switch regarding the improvement in relapse outcomes. Patients in the FNG cohort experienced sustainably fewer relapses during the follow-up period after the switch compared the iDMT cohort. Importantly, switching to FNG was more effective in delaying time to first relapse when compared with iDMTs.
Keywords: Fingolimod; disease modifying treatment; treatment switch; glatiramer acetate; beta interferon